Dye-doped cholesteric liquid crystal light shutter with a polymer-dispersed liquid crystal film. (November 2016) - Oh, Seung-Won; Baek, Jong-Min; Heo, Joon; Yoon, Tae-Hoon
Abstract: A light shutter, which consists of a dye-doped cholesteric liquid crystal (ChLC) layer and a polymer-dispersed liquid crystal (PDLC) film, for simultaneous control of haze and transmittance is demonstrated. In the opaque state, it can not only provide a black color by using the dye-doped ChLCs but also hide the objects behind the display panel by using the PDLC film. The proposed light shutter shows a high haze value of 90.7% with a low specular transmittance of 1.20%. By switching the proposed light shutter placed at the back of a see-through display, we can choose between the see-through mode and the high-visibility mode in a see-through display. Graphical abstract: Highlights: We propose a light shutter consisting of a dye-doped ChLC layer and a PDLC film. We can simultaneously control haze and transmittance. It can provide the black color and hide the objects behind the display panel.